2001
DOI: 10.1007/bf02867577
|View full text |Cite
|
Sign up to set email alerts
|

Value of ascitic fluid cholesterol and serum-ascites albumin gradient in differentiating cirrhotic and malignancy related ascites

Abstract: In a perspective study, the asci~c fluid and serum concentration of totel cholesterol, total proteins and albumin in a group of 45 patients was studied. Patients with nonmalignant or cirrhotic mites were compared with patients having malignancy related ascites and it was proved that the escitic fluid cholesterol and the serum ascites albumin gradient helped to differentiate cirrhotic from malignant ascites. These two parameters showed a remarkable relationship to the presence/absence of malignancy. Non maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…Almost similar result was also reported by Anita R. Bijoor et al 13 studied the ascitic fluid and serum concentration of total cholesterol, total proteins and albumin in a group of 45 patients. Non-malignant ascites patients had ascitic fluid cholesterol values of 19.41±8.33 mg/dl, as against the malignancy related ascites patients, who showed levels of 95.87±1.24 mg/dl.…”
Section: Discussionsupporting
confidence: 86%
“…Almost similar result was also reported by Anita R. Bijoor et al 13 studied the ascitic fluid and serum concentration of total cholesterol, total proteins and albumin in a group of 45 patients. Non-malignant ascites patients had ascitic fluid cholesterol values of 19.41±8.33 mg/dl, as against the malignancy related ascites patients, who showed levels of 95.87±1.24 mg/dl.…”
Section: Discussionsupporting
confidence: 86%
“…Also the cut-off values obtained in the present study for ascitic fluid lipids and protein were not similar to previous studies [16, 17, 21], whereas the cut-off value for SAAG was reliable, as confirmed by previous studies [18–20, 27].…”
Section: Discussionsupporting
confidence: 59%
“…Some of recent studies had showed higher diagnostic significance of Ascitic Fluid Cholesterol and Serum Ascites Cholesterol Gradient in ascites due to malignancy [1417]. The present study was done to reveal the diagnostic utility of serum ascites lipid gradients in patients with ascites and compared it with standard SAAG criteria, to know whether it has a higher diagnostic yield.…”
Section: Introductionmentioning
confidence: 94%
“…[1] Several studies have proved an elevated ascitic fluid cholesterol levels in patients with malignant ascites but not in tuberculous ascites. [2] Along with it, serum ascites cholesterol gradient (SACG) too aids in differential diagnosis of ascites. [3,4] However only a few studies have related the serum & ascitic fluid -total protein, albumin, cholesterol & their gradients (SAAG, SACG) in differential diagnosis of ascites Hence we took up this study with primary objective to differentiate ascites due to hepatic cirrhosis and tuberculosis peritonitis by estimating Serum & Ascitic fluid -Total protein, Albumin, Cholesterol & their gradients (SAAG, SACG).…”
Section: Introductionmentioning
confidence: 99%